General theorems of the alternative in variable ordering structures - Jahn, Johannes (Journal of Nonlinear and Variational Analysis, 2021)
This paper presents two new theorems of the alternative, which can be used for the proof of necessary optimality conditions for nonconvex optimization problems like discrete-continuous problems and for vector optimization problems with variable orderings.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Farkas' lemma; Necessary optimality conditions; Nonconvex optimization; Theorems of the alternative; Vector optimization